Urgent Problems of References Arrangement in Research Documents - N. V. Avdeeva; I. V. Sus (Открытое образование (Москва), 2020)
The purpose of research. Currently, the problem of plagiarism is quite relevant and affects the scientific and educational spheres. Thus, the experts of the Russian State Library have organized special research, and they are issuing a series of articles devoted to that activity. Within the framework of fighting plagiarism and other negative phenomena, it becomes necessary to highlight mostly wide-spread problems of reference-arrangement for research papers, and to outline possible solutions for them. We will consider this issue in the first article of the series.Materials and methods. In order to achieve the aforementioned target the article uses the results of the plagiarism tests for research papers carried out by the Russian State Library with the help of specially designed software “Antiplagiat.RSL”.Results. The common defects of research papers are: inclusion of fictitious sources into the reference list, lack of homogeneity in reference arrangement, inadequate references to the groups of sources, quoting the derivative sources instead of the original one, spreading false information because of blind copying other researchers’ mistakes. Plagiarism tests carried out over scientific texts helped to identify the most frequent incorrect borrowings (overlapping wording of conclusions and generalizations, the same sentences used for describing results and methods, as well as word – for – word reproduced literature reviews). The documents revealed to become sources for such plagiaristic borrowings would often be works of research advisors and other authoritative specialists, candidate dissertation theses close in theme or structure, earlier publications of authors themselves, including those written in co-authorship.Conclusion. Numerous flaws are made by emerging authors due to the lack of knowledge, that is why students’ and post-graduates’ efficient training in work with GOST state standards as well as the quality of educational and methodological literature in research-paper writing would be of use. The article offers ways of improvement for research publication arrangement and specialized software products destined to make reference arrangement automatic.